Digital Transformation of Islamic Religious Education in the AI Era: Strategies, Governance, and a Multi-Level Framework - Siti Faridah, Eva; Fitriana, Winda Nidya Putri; Djuanda, Isep; Laelasari, Eda; Sayekti, Siskha Putri (Faculty of Tarbiyah and Education, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2026)
Purpose – This study synthesizes evidence on digital transformation strategies in Islamic Religious Education (IRE; Indonesian: Pendidikan Agama Islam, PAI) in the era of artificial intelligence (AI) and formulates a multi-level implementation framework that safeguards learning quality, the authenticity of religious knowledge, and academic integrity. Design/methods/approach – This systematic review followed PRISMA 2020 and covered publications from 2015-2025, with primary searches conducted in Scopus and Web of Science, supplemented by search updates and citation tracking. A total of 57 studies were synthesized thematically according to technology, pedagogical design, learning outcomes, implementation conditions, and ethical and governance issues. Findings – Six evidence clusters were identified: classroom digital pedagogy; AI and learning analytics; technology-supported Qur'anic learning; readiness and acceptance; institutional leadership and policy; and ethics and governance. Evidence was more consistent for cognitive and skills outcomes than for affective-spiritual and character outcomes. Success was associated more closely with pedagogical design, educator competence, institutional support, learner literacy, and governance guardrails than with any single technology. Practical Implications – The framework provides guidance for educators, program managers, institutional leaders, and policymakers to align digital and AI adoption with pedagogical design, educator competence, learner literacy, institutional support, and governance guardrails.